Lo Tiwa: Ritual of Human and Non-Human Relationship in Lembata Regency, East Nusa Tenggara Province, Indonesia - Kewuel, Hipolitus Kristoforus; Langoday, Thomas Ola; Rongan, Wilhelmus Ola; Kraeng, Pankrasius Olak; Tugang, Noria Anak; Aileen, Aileen (Universitas Andalas, 2024)
This research focuses on the perspective of indigenous ecologies to see how the Lembata people maintain and care for their relationship with nature. The research located in the Lebatukan District highlands area of Lembata Regency in East Nusa Tenggara Province of Indonesia. The Lo Tiwa ritual is carried out by the Lembata people when pests attack their crops. When snails were attacking rice plants, people realized that they could eradicate the slugs through modern ways. However, they also realized that with the pesticide technology, the life of snails was threatened with extinction, which is considered unwise in preserving the local environment. Instead, they raised this issue on the altar of the Lo Tiwa ritual. In this way, preserving the relationship between humans and nature has happened, which is an integral part of environmental studies. Snails as pests are not killed, and rice plants are free from pests. In the Indonesian context, this research finds its context in efforts to promote a culture where the government wants to place culture, including rituals, as one of the essential forces in development. Apart from rituals, other cultural promotion objects include; oral traditions, manuscripts, customs, folk games, traditional sports, traditional knowledge, arts, and languages.